To be structured, or unstructured, fifty years of slings and arrows - Dervieux, Alain (Comptes Rendus. Mécanique)
This paper is not a review, but narrates the personal experiences (nearly fifty years) of the author concerning unstructured mesh, a well debated theme during these years.